Communication Behaviour of Women Vegetable Growers of Nainital District of Uttarakhand - Verma, Deepika (Indian Journal of Extension Education, 2017)
Aresearch on communication behaviour of women vegetable growers of Nainital district of Uttarakhand was undertaken  to find out information processing behaviour and approaches used by the women vegetable growers. The study was  conducted in six villages of Community Development Blocks, Haldwani, Ramnagar and Dhari in Nainital district of  Uttarakhand. Data were collected through pre-tested semi- structured interview schedule and Focous Group Discussion  from 150 women vegetable growers. The findings of the study revealed that the personal cosmopolite sources, which are  part of farming community, live with the farmers, being aware of farmers' problems, providing new technologies, and  having close supervision, can play significant role for bringing agricultural development in the area.
Keywords: Communication sources; communication behaviour; communication approach; farm women; vegetable cultivation